Group G streptococci in healthy school-children and in patients with glomerulonephritis in Trinidad. - Reid, H. F. (Cambridge University Press, 1985)
The group G streptococcus has generally not been considered a prominent pathogen. In a 1982 study of the colonization rate by beta-haemolytic streptococci in apparently healthy children, age 5-11 years, 25 of 69 isolates belonged to group G. This surprisingly high rate of group G colonization (14.3%) led to a retrospective study of school surveys in 1967 which showed that the colonization rate with this organism was 2.3% (range 1.3-3.5%). A review of bacitracin-sensitive streptococcal isolates from hospital admissions of patients with acute glomerulonephritis (AGN), rheumatic fever, and their siblings, between January 1967 and July 1980, was conducted. Of 1063 bacitracin-sensitive isolates, 63 were group G, and 52 of these were isolated from AGN patients and their siblings, i.e. 7 from skin lesions of AGN patients, 40 from the throats of siblings and only 5 from the skins of the siblings. The other 11 group G isolates were from rheumatic-fever patients and their siblings. Thus, the group G colonization rate fluctuates in the population. The isolation of only group G streptococci from skin lesions of patients with AGN suggests a possible association between group G streptococcal pyoderma and acute post-streptococcal glomerulonephritis.